Pengembangan Metode Analisis Amoksisilin yang Selektif dan Tidak Dipengaruhi Keberadaan Produk Degradasinya - REHANA REHANA; HANIF HAFIIDH SETYO NUGROHO; VITIS VINI FERA RATNA UTAMI (Fakultas Farmasi Universitas Pancasila, 2014)
Assay of amoxycillin level in suspension form using spectrophotometry method at maximum wavelength around 291 nm is predicted to provide accurate and selective result because it is not interferred with its degradation products. This research aimed to obtain the predicted result. This research employed laboratory experimental method which included the process of measuring of maximum wavelength and operating time measurement, making of standard curve by measuring absorbance of amoxycillin standard solution at 40, 50, 80, 100 and 120 ppm at 290 nm and testing the selectivity and accuracy. Selectivity test was done by comparing UV spectrum and maximum absorbance of 1 mg/mL amoxycillin standard solution and 125 mg/5 mL amoxycillin suspension immediately after reconstitution with the one that was stored 9 days. Accuracy test was conducted by standard addition method using 1 mL amoxycillin suspension that was stored 9 days added by 1 mL 6260 ppm amoxycillin standard solution. Assay of amoxycillin on amoxycillin suspension by UV spectrophotometry at 290 nm using NaOH 0,1 N as solvent gave selective and accurate result with 97,36% recovery and it is not interfered with by its degradation product.